Stationary Cycling Exercise With Virtual Reality to Reduce Depressive Symptoms Among People With Mild to Moderate Depression: Randomized Controlled Trial - Na Zhang; Chenlu Hong; Yuejia Wang; Haiqin Chen; Yueli Zhu; Miao Da; Zhongxia Shen; Xudong Zhao; Jiali Xu; Jiaxiu Sheng; Yanan Luo; Meiying Xu (Journal of Medical Internet Research, 2025)
Abstract BackgroundVirtual reality (VR) stationary cycling provides a potential solution to enhance adherence and reduce depressive symptoms, particularly for people with depression. However, high-quality evidence is needed to support its implementation in clinical practice. ObjectiveThis study evaluated the clinical effects of a 12-week VR-based stationary cycling program on depressive symptoms in sedentary adults with mild to moderate depression. MethodsThis study is a 12-week, 3-arm randomized controlled double-blind trial. Participants (aged 18‐60 years) with depression were recruited from a clinic and randomly assigned (1:1:1) to the VR high-intensity stationary cycling, VR moderate-intensity stationary cycling, or non-VR moderate-intensity stationary cycling group to receive face-to-face intervention. The primary outcome was the change in depressive symptoms measured by the Hamilton Depression Rating Scale (HAMD-17) between baseline and 12 weeks. Response rate, remission rate, satisfaction, compliance, and adverse events were assessed post intervention. Outcomes were analyzed using an ITT approach. ResultsBetween January 2023 and June 2024, a total of 114 participants were enrolled and randomly assigned to 3 groups (38 per group), with 101 completing the trial (33 in non-VR moderate-intensity stationary cycling, 35 in VR moderate-intensity cycling, and 33 in VR high-intensity cycling). All 114 randomly assigned participants were included in the ITT analysis. After the 12-week intervention, all groups showed significant improvements in depressive symptoms, as reflected by the mean difference in HAMD-17 scores within groups from baseline to week 12: non-VR moderate intensity (mean difference within groups: 10.9, 95% CI 9.3-12.5; response rate: 58%, remission rate: 40%); VR moderate intensity (mean difference within groups: 14.2, 95% CI 12.7-15.8; response rate: 84%, remission rate: 74%); and VR high intensity (mean difference within groups: 14.4, 95% CI 13.0-15.8; response rate: 92%, remission rate: 74%). VR-based groups showed greater reductions than the non-VR group (mean difference between groups: 3.3, 95% CI 1.9-4.9, for VR moderate-intensity; mean difference between groups: 3.9, 95% CI 2.5-5.2, for VR high intensity). No significant difference in symptom improvement was found between the 2 VR groups, although the moderate-intensity group reported higher satisfaction. ConclusionsThe VR stationary cycling program is an efficacious health intervention for alleviating depressive symptoms in participants with mild to moderate depression. These findings could facilitate incorporating VR health intervention into clinical practice, enhance the response of cycling-based interventions, and improve patient adherence, supporting its use as a complementary treatment for depression.